Antegrade wire escalation for chronic total occlusions in coronary arteries: simple algorithms as a key to success. Issue 9 (September 2016) - Maeremans, Joren; Knaapen, Paul; Stuijfzand, Wynand J.; Kayaert, Peter; Pereira, Bruno; Barbato, Emanuele; Dens, Jo
Abstract : Aims: Antegrade wire escalation (AWE) remains the method of choice for tackling chronic total occlusions (CTOs), especially for lesions with low J-CTO score. To increase the number of operators which treat CTOs and increase AWE success rates, there is a need for a clear, algorithmic approach. We report the results of a simple AWE algorithm with new guidewire technology in coronary CTOs. Methods: Hundred consecutive CTO lesions selected for AWE as the primary strategy were included in five Benelux centers. The algorithm follows a step-wise increase in guidewire tip load. Lesions were categorized according to the J-CTO score. Primary endpoint was successful guidewire crossing. Results: No differences in baseline demographics were present between successful and unsuccessful procedures. Overall, in 75% of the lesions AWE resulted in successful crossing. AWE success rates in easy, intermediate, difficult and very difficult CTOs were 83, 86, 71 and 43%, respectively. 46% could be crossed using a soft guidewire only. An additional success of 34 and 60% could be reached with an intermediate and stiff guidewire, respectively. Adding additional techniques resulted in 88% overall success. Procedure and fluoroscopy times, radiation doses and use of contrast were within highly acceptable ranges (67 ± 39 min, 27 ± 19 min, 1.7 ± 1.3 Gy, 264 ± 123 ml). Conclusion: The algorithm and new wire technologies led to high success rates. AWE as a standalone procedure is highly successful in J-CTO 0-1. Low- and intermediate-volume CTO operators should try to implement a systematic approach in their CTO procedures, especially for lesions with low J-CTO scores. Adding additional techniques further increases these success rates.